Hormonal status in women of reproductive age with nonspecific vaginitis - Ryazanova, O.D. (Medicni Perspektivi, 2023)
Bacterial vaginosis and aerobic vaginitis are the most common problems among gynecological pathology in women of reproductive age. The share oh nonspecific vaginitis is affected by stress, which affects the state of a woman’s hormonal system. However, the relationship between hormonal changes, exposure to chronic stress and nonspecific vaginitis has not been fully established, which is up-to-date task. Aim of study is to study changes in the levels of gonadotropic and sex hormones, as well as cortisol in women of reproductive age with aerobic vaginitis and bacterial vaginosis. 160 women (100%), divided into 2 clinical groups with subgroups were examined: the main group – 94 (58.8 %) patients with nonspecific vaginitis, who received treatment according to developed clinical diagnostic algorithms and schemes. The comparison group included 66 (41.2%) patients with nonspecific vaginitis, who received treatment according to known protocols. In the process of examining groups, the following research methods were used: general (collection of complaints and anamnesis, gynecological examination, assessment of microscopy of vaginal smears according to the Amsel, Nugent and Donders criteria), laboratory (method of determining the level of follicle-stimulating hormone, luteinizing hormone, prolactin, estradiol, cortisol), statistical. According to the study results it was found that women of reproductive age with nonspecific vaginitis are likely to have elevated levels of follicle-stimulating, luteinizing hormones, prolactin, cortisol and significantly reduced estradiol levels compared to healthy individuals. In conclusion, the results indicate changes in gonadotropic and sex hormones in women with nonspecific vaginitis towards the increased levels of follicle-stimulating, luteinizing hormones, prolactin, cortisol and decreased levels of estradiol. Such hormonal changes indicate depletion of the hypothalamic-pituitary-genital system, which occurs under the influence of chronic stress on the body of women of reproductive age with nonspecific vaginitis.